Prevalence and influencing factors of oral frailty in older adults: a systematic review and meta-analysis - Zhou, Yutong; Zhou, Li; Zhang, Wen; Chen, Yao; She, Keyi; Zhang, Hongtao; Gao, Yue; Yin, Xinhong (Frontiers in Public Health, 2024)
ObjectiveThis study aimed to conduct a systematic review and meta-analysis, assessing the pooled prevalence and influencing factors of oral frailty in older people to assist healthcare professionals in enhancing their understanding of this condition and formulating efficient interventions.MethodsThis systematic review was performed based on the Preferred Reporting Items for Systematic Reviews and Meta-analyses Statement (PRISMA) guidelines. We searched PubMed, Web of Science, The Cochrane Library, Embase, CINAHL, ProQuest, the National Knowledge Infrastructure (CNKI), WAN FANG DATA, VIP Information, SinoMed and Scopus for literature published in English or Chinese from inception to June 19, 2024. Subsequently, we evaluated the potential for bias in the cross-sectional studies that met our criteria through the Agency for Healthcare Research and Quality (AHRQ) tool. In contrast, we utilized the robust Newcastle-Ottawa scale for cohort and case–control studies. We performed statistical analyses using STATA 17 software. Prevalence was studied using a meta-analysis of a single proportion. For influencing factors, dichotomous variables were expressed as odds ratios (ORs) and 95% confidence intervals (Cls), and continuous variables were expressed as weighted mean differences (WMDs) and 95% confidence intervals (Cls).ResultsInvestigation into 17 studies encompassing 24,983 participants discovered a striking 28% overall prevalence rate for oral frailty among older individuals (95% CI 20–36%, p < 0.001). Upon assessing the literature’s quality, nine articles acquired high ratings; all others received medium ratings. These findings imply a complex interplay among biological, socio-economic, lifestyle, and disease-pharmacological factors in the manifestation of oral frailty in older adults.ConclusionOral frailty is prevalent in older adults and is impacted by diverse factors. Enhanced surveillance and effective interventions for oral frailty are required in older cohorts.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024544552, identifier CRD42024544552.